Spontaneous spinal osseous epidural arteriovenous fistula with long segments of prominent epidural venous drainage causing severe compressive thoracic myelopathy successfully treated with combined endovascular and surgical treatments: A case report and review of the literature - Iampreechakul, Prasert; Tirakotai, Wuttipong; Lertbutsayanukul, Punjama; Thammachantha, Samasuk; Siriwimonmas, Somkiet (Asian Journal of Neurosurgery, 2020)
The authors describe an extremely rare case of spinal osseous epidural arteriovenous fistulas (SOEAVFs) with unique characteristic features. A 25-year-old man presented with progressive weakness and paresthesia of the lower extremities for 1 month. Magnetic resonance imaging of the thoracic spine showed an extradural dilated vascular flow void structure extending from T4 to T8 levels with abnormal hyperintense T2 signal from T6 to T8 levels. Magnetic resonance angiography and spinal angiography revealed unique features of SOEAVF supplied by multiple small arterial feeders of intercostal arteries converging into a dilated round venous sac corresponding to a bony defect of T7 lamina and spinous process. The venous drainage directly drained into prominent epidural venous plexus extending from the level of T4 to T8 without intradural venous drainage, causing severe compressive myelopathy. Transarterial embolization was performed using N-butyl cyanoacrylate through the main feeder. Subsequently, he successfully underwent laminectomy and total excision of the fistula and large epidural draining venous plexus. Histopathology confirmed spinal vascular malformations with evidence of previous embolization. He gradually improved until being ability to walk independently 3 months later. Follow-up spinal angiography confirmed complete resection of SOEAVF. The patient has remained clinically asymptomatic 5 years after operation.
Keywords: Compressive myelopathy; round venous sac; spinal osseous epidural arteriovenous fistula; surgical treatment; thoracic spine